Predisposing Factors for Coronary Vasospasm in Prinzmetal Angina - A Literature Review - Znamirowska, Patrycja; Mularczyk, Klaudia; Paszkowska, Monika; Karaban, Łukasz; Kupis, Magdalena; Jakubiak, Anna; Miśkiewicz, Joanna; Borawski, Michał; Ciuła, Aleksandra; Kuźnieców, Tadeusz (Quality in Sport, 2025)
Introduction and Purpose: Prinzmetal angina or vasospastic angina (VSA) is cardiac ischemia caused by spasm of the coronary arteries. It is characterized by chest pain at rest and ST-segment elevation on electrocardiographic (ECG). Vasospasm can be focal or diffuse, but VSA often remains undiagnosed. The purpose of this study is to present risk factors for coronary vasospasm in Prinzmetal angina based on the available literature. Materials and Methods: A literature review was conducted from the PubMed database, covering studies from 2015-2025. Meta-analyses and randomized controlled trials were analyzed. Key phrases such as “Prinzmetal angina,” “risk factors” and “angina pectoris” were used. Selected papers were evaluated for results and conclusions. Description of the State of Knowledge: Symptoms of VSA include recurrent chest pain, relieved by nitrates. They occur at rest, mainly at night. VSA can be asymptomatic, leading to arrhythmias or sudden cardiac death. Diagnosis requires criteria, including confirmation of coronary artery spasm with more than 90% stenosis, observed during provocative testing. Conclusions: VSA is associated with genetic and environmental factors, such as smoking, hyperthyroidism and chronic inflammation. Despite its coexistence with coronary artery disease, its presence does not always negatively affect prognosis. Further research may contribute to better diagnosis and personalization of therapy.